Placebo-resistant gut bacteria: Akkermansia muciniphila spp. and Familial Mediterranean fever disease - Pepoyan, Elya; Marotta, Francesco; Manvelyan, Anahit; Galstyan, Artak; Stepanyan, Lena; Grigoryan, Hasmik; Grigoryan, Liana; Mikayelyan, Mikayel; Balayan, Marine; Harutyunyan, Natalya; Mirzabekyan, Susanna; Tsaturyan, Vardan; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Despite numerous investigations into the impact of drugs/probiotics on the gut microbiota composition in Familial Mediterranean Fever (FMF) patients, the question remains unresolved as to whether there exists a significant bacterial diversity(ies) independent of the placebo effect that can be reliably considered in clinical and nutritional trials.This study represents the inaugural analysis of the placebo's influence on the gut microbiota of both healthy individuals and FMF-afflicted men, utilizing previously collected data from PhyloChip TM DNA-microarray experiments. A total of 15 healthy and 15 FMF male volunteers, aged 18 to 50, participated in this partially randomized placebo trial, accessible through the GEO Series accession number GSE111835. Key findings from current investigations include: i. the anticipated divergence in gut bacteria resistance to placebo between healthy and FMF individuals, ii. a minor impact of placebo on gut bacterial diversities in healthy individuals, with Enterobacteriaceae diversities identified as placeboresistant among "healthy" gut bacteria, and iii. the comprehensive influence of placebo on all bacterial phyla in the gut microbiome of FMF patients, extending to nearly all bacterial genera, except for the resilience of gut Akkermansia muciniphila spp. to placebo in FMF patients.This study underscores the susceptibility of Faecalibacterium, Blautia, and Clostridium genera to placebo. Consequently, this investigation holds significance for the proper design of placebocontrolled trials and establishes a foundation for further exploration of the gut-brain axis. Furthermore, it contributes valuable insights to discussions regarding proposals for probiotic therapies, particularly focusing on Faecalibacterium spp., Blautia spp., and Clostridium spp.